The genus Sitothrips (Thysanoptera: Thripidae) with a new grass-living species from southern Iran - Minaei, Kambiz; Mound, Laurence (Zootaxa, 2014)
One of the generic characters given by zur Strassen (2003) for species of the genus Sitothrips Priesner (1931) is the presence of 2-segmented maxillary palps. In contrast, a new species of this genus is described below from Iran in which the maxillary palps are clearly 3-segmented (Fig. 5). The genus was erected for arabicus Priesner from Egypt, a species now recorded widely among countries around the Mediterranean, from Morocco to southern Russia. Three further species are listed in Sitothrips: almargeniensis Titschack from Spain and Portugal, lindbergi zur Strassen from the Canary Islands and Morocco, and calcaratus (Savenko) from southern Russia. The identity of the latter species remains in some doubt as, in contrast to the other species, it was described as wingless and lacking ocelli (Savenko 1944), but zur Strassen (2003) provided an illustrated key to the other three species.